Physiological and Anatomical Changes Induced in Wheat (Triticum aestivum cv. Hendrix) by Lead Stress - Akçin, A.; Aytaş Akçin, T. (Centenary University, 2025)
LED (Pb), a by-product of industrial activity and urban wastewater, poses a significant threat to crops, ecosystems and human health. This study examined the effects of Pb stress on the physiology and anatomy of Triticum aestivum cv. Hendrix, a wheat cultivar. Wheat plants were exposed to Pb concentrations of 0, 5, 10, and 15 mM for three weeks. Exposure to lead stress significantly decreases the levels of various photosynthetic pigments, including total chlorophyll, total carotenoids, chlorophyll a, and chlorophyll b. The content of malondialdehyde (MDA) content, a marker of lipid peroxidation, increased significantly with increasing Pb concentrations. Anatomical changes in Pb-stressed plants included decreased root cortex and endodermis thickness, increased intercellular spaces in cortical tissues, increased collenchyma thickness in stems, decreased vascular element number and trachea diameter in stems, and reduced bulliform cell size and sclerenchyma, xylem, and phloem thickness in leaves. These changes suggest that Pb stress may disrupt vascular development in root, interfere with water and nutrient transport in the stems, and reduce photosynthetic capacity in the leaves. The accumulation of Pb in the vascular bundles suggests that these tissues may be particularly sensitive to Pb stress. Overall, the results show that Pb stress causes a variety of anatomical changes in T. aestivum cv. Hendrix, which may represent adaptive responses to Pb stress. © 2025, Centenary University. All rights reserved.
Keywords: Anatomical Changes; Heavy Metals; MDA Content; Photosynthetic Efficiency; Wheat